Media Education Quartet Card Play on Reproductive Health Learning in Adolescents - Fazrin, Intan; Suci Anggraeni; Nur Yeny Hidajaturrokhmah; Retno Palupi Yonni Siwi; Candra Wahyuni (Journal Of Nursing Practice, 2023)
Background: The low knowledge of adolescents about reproductive health is due to a variety of factors, among others customs, culture, religion, and the lack of information from the right sources. This lack of knowledge will lead to various impacts that are especially detrimental to the youth group and their families. Preparing adolescent women with adequate knowledge of reproductive health is crucial for optimizing the quality of life of adolescents in the future. Purpose: This study aimed to analyze the influence of quartet card game media education on reproductive health on knowledge in adolescents. Methods: The study uses a pre-experimental research design and one group pre-posttest design. The population in this study is the entire youth SMP YBPK Kota Kediri as many as 50 respondents, sample 24 respondents selected using accidental sampling technique. Free variables are educational media card games about reproductive health and bound variables are knowledge. Quartet card media educational instruments use SOP, and knowledge using questionnaires. Data analysis using the Wilcoxon test. Results: The results of the statistical tests showed that the value of Asymp.Sig. (2-tailed) is 0.01 less than 0.05, then Ha is accepted, meaning there is an influence of the educational media of the quartet card game on reproductive health on knowledge in adolescents. Conclusion: Quartet media can create enjoyable learning situations that can enhance adolescent knowledge about reproductive health.